Specific type of childhood trauma and borderline personality disorder in Chinese patients - Wu, Yanru; Zheng, Yuchen; Wang, Jijun; Zhang, Tianhong (Frontiers in Psychiatry, 2022)
Background: Childhood maltreatment is a known risk factor for the development of mental disorders. An extensive body of literature about childhood maltreatment and mental health has been developed in wealthy countries, but information about this connection is lacking in developing countries including China. Aims: To explore the possible relationship between specific types of childhood maltreatment and borderline personality disorder in patients with mental disorders in China. Methods: A survey was conducted in 2006, involving over 3402 Chinese individuals aged 18-60 years who were randomly selected from the outpatients in Shanghai Mental Health Center. The patients were screened with Personality Diagnostic Questionnaire and childhood maltreatment was assessed using the Childhood Trauma Questionnaire. The final sample comprised of 178 patients with borderline personality disorder, 178 patients with other personality disorders, and 178 patients without personality disorders. Results: In Chinese patients, compared to other personality disorders, patients with borderline personality disorder are more likely to have childhood maltreatment. Emotional maltreatment (emotional abuse and neglect) was the strongest predictor for borderline personality disorder. Female gender and sexual abuse are significant predictors of the self-harm/ suicidal risk of borderline personality disorder patients. Conclusion: This is a pioneering study conducted in a large set of Chinese clinical sample with paired controls to establish and compare the associations between specific childhood maltreatment and borderline personality disorder. Further studies in this field are necessary to elucidate the mechanism of how various types of childhood trauma have influenced personality disorders.